Macroscopic Hematuria—A Leading Urological Problem in Patients on Anticoagulant Therapy: Is the Common Diagnostic Standard Still Advisable?. (1st April 2012) - Antoniewicz, Artur A.; Zapała, Łukasz; Poletajew, Sławomir; Borówka, Andrzej
Abstract : All urological standards of care are based on the past definition of the clinical importance of macroscopic hematuria. The aim of the study was to assess the phenomenon of iatrogenic hematuria in current clinical practice and analyze its origins in patients receiving anticoagulant drugs. Retrospective analysis of clinical documentation of 238 patients that were consulted for hematuria in 2007–2009 by 5 consultant urologists was performed. In the group of 238 patients with hematuria, 155 (65%) received anticoagulants. Abnormalities of urinary tract were found in 45 (19%) patients. Estimated cost of a single neoplasm detection reached the value of 3252 Euro (mean 3-day hospitalization). The strong correlation between the presence of hematuria and anticoagulant treatment was observed. Authors suggest to redefine the present and future role of hematuria from a standard manifestation of serious urological disease to a common result of a long-term anticoagulant therapy.